Seed yield of mungbean as affected by variety and plant spacing in Kharif-I season - Kabir, MH; Sarkar, MAR (Journal of the Bangladesh Agricultural University, 2010)
An experiment was carried out to study the effect of variety and planting density on the yield of mungbean in Kharif-I season (February to June) of 2003. The experiment comprised five varieties viz. BARIMung-2, BARIMung-3, BARIMung-4, BARIMung-5 and BINAMung-2 and three spacing of planting viz. 30 cm × 10 cm, 20 cm × 20 cm and 40 cm × 30 cm. The experiment was laid out in a randomized complete block design with three replications. It was observed that BARIMung-2 produced the highest seed yield and BINAMung-2 did the lowest. Plant spacing of 30 cm × 10 cm produced the highest seed yield of mungbean while 40 cm × 30 cm spacing produced the lowest seed yield. BARIMung-2 planted at a spacing of 30 cm × 10 cm gave the maximum seed yield. Keywords: Mungbean; Variety; Plant spacing; Yield DOI: 10.3329/jbau.v6i2.4817 J. Bangladesh Agril. Univ. 6(2): 239-244, 2008